Influence of Degree of Saturation on Soil–Pile Interactions for Piles in Expansive Soils - Kuo Chieh Chao; A-Nanya Chaladthanyakit; Taskid Hossain Asif (Applied Sciences, 2025)
Conventional designs of pile foundations for houses on expansive soils adopt conservative approaches by using swelling pressure measured in oedometer tests to compute pile uplift force. However, in practice, piles are often installed in unsaturated soils, where changes in moisture content influence soil behavior. Increasing moisture in expansive soils reduces matric suction, increases soil volume, and induces swelling pressure, all of which affect uplift shear stress. This study investigates the impact of varying degrees of saturation on pile uplift force through a series of laboratory tests on single-pile models. The results of the experimental investigation indicate that uplift force developed along the pile shaft due to the wetting of expansive soils exhibits a hyperbolic trend. A significant portion of the uplift force developed during the early stage of the heaving process. Back-calculation analyses using theoretical equations reveal that the coefficient of uplift, α, and the swelling pressure ratio, β, increases as the initial degree of saturation of soil specimens increases, with a change of less than 10% within the tested range. These findings suggest that constant values of the α and β parameters can be used for pile design in expansive soils, even under unsaturated conditions. Nonetheless, the influence of other factors, such as pile dimensions, pile materials, and soil properties, on the α and β values should be investigated to improve the accuracy of pile design in expansive soil conditions.